The use of Gentani approach for benchmarking resource efficiency in manufacturing industries - Sarfraz, Shoaib; Jolly, Mark R.; Salonitis, Konstantinos (Springer, 2023)
The majority of today’s manufacturing processes are based on well-developed and well-established procedures that are characteristics of mature technologies. The manufacturing industries have not evolved significantly over time because of recent economic, environmental, and societal advances at an unprecedented rate. As a result, there are numerous challenges and opportunities available, especially regarding resource efficiency. The majority of industrial processes consume far more energy than the theoretical minimal process energy requirements. This paper aims to develop a theoretical framework utilising the Gentani approach whilst targeting the minimum resources needed to carry out a process for use by manufacturing industries. The resource efficiency (exergy) metric has also been discussed that can be used as a tool to evaluate the efficiency of industry, depicting a more holistic level of energy and material consumption. The framework will help manufacturing industries in lowering costs and remain competitive by improving resource efficiency, aimed at reducing resource use and providing value delivery. The study will also assist in transforming these industries into resource-efficient modern manufactories in line with the Net-Zero 2050 agenda.
Keywords: manufacturing; net zero; Gentani; resource efficiency; exergy